Ideas of Carrying Out Character Education in Speaking 1 Class - Putu Ayu Prabawati Sudana (Bandar Lampung University (UBL), 2013)
To be able to speak properly in one language, one probably only thinks about language expressions, vocabulary, grammar, pronunciation and intonation, that those five components are adequate to be mastered. Yet actually, we can never put aside some other aspects in speaking, such as the role, age or status of the interlocutor, the non verbal behavior which we perform and the setting in which we are speaking. Unfortunately, nowadays it seems that not all students are fully aware of those aspects. Sometimes their speaking style does not show respect to the people whom they talk to. Now to gain their awareness of those aspects and for them to be able to speak English correctly and properly based on the circumstance, some ideas can be carried out in class, namely giving examples of formal and casual conversations, giving a few language expressions for one function which range from the more formal until the less formal, giving cued conversations with different interlocutors and settings as exercise, giving exercise of identifying proper or polite expressions and correcting utterances, and exposing students with non verbal communication which may include knowledge of cross cultural understanding. In relation to character education, those ideas will contribute to the pillar of respect, that the students should respect the people who they talk with and this is manifested in their choice of verbal and non verbal expressions.